Outcome of Primary Percutaneous Coronary Intervention Among Patients of Complete Atrioventricular Block with Acute Inferior St-Elevation Myocardial Infarction - Sohail Rashid, Zain Mehmood Butt, Muhammad Suleman Khan, Muhammad Saeed Afridi, Shahzad Majeed Bhatti, Muhammad Shahid, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To assess the outcomes of primary percutaneous coronary intervention among patients of complete atrioventricular block with acute inferior ST-elevation myocardial infarction Methods: We conducted an observational study of patients with CAVB and STEMI who underwent Primary PCI at interventional cardiology department, national institute of cardiovascular diseases Karachi during the period from January 1, 2022 to July 31, 2022. The primary outcomes were in-hospital mortality and CAVB resolution. Results: A total of 100 patients were included in the study. The mean age was 60.63±5.63 years, and 61% were male. The median door-to-balloon time was 89.96±17.97 minutes. In hospital mortality rate was 4%. CAVB was resolved in 93%. Conclusion: For patients with CAVB and STEMI, Primary PCI is a safe and successful treatment with a low rate of in-hospital mortality. These findings support the use of primary PCI in this patient population. Keyword: Primary PCI, CAVB, STEMI